CASE STUDY OF IMPROVING OPERATIONAL EFFECTIVENESS OF CONGREGATE MEAL PROGRAM FOR ELDER IN CHIAYI COUNTY - Lu, Te-Tsai; Chen, Wen-Chun (Graduate Program of Universitas Tarumanagara, 2025)
The issue of population aging in Taiwan is becoming increasingly severe, necessitating simple dining solutions such as senior cafeterias to facilitate social interaction among the elderly. These cafeterias aim to provide the elderly with basic care for their health, daily live, psychological and social well-being, and even leisure education. However, despite the efforts put into these programs, numerous challenges and areas for improvement persist. This research focus on the senior cafeterias in Chiayi County as a case study to investigate the current status of community-based congregate meal services for the elderly and explore ways to enhance their operations and benefits. The study begin with surveys and in-depth interviews with key stakeholders involved in the operation of these cafeterias. Following data analysis, recommendations are presented for improving the operation of senior cafeterias in Chiayi County. These recommendations encompass strategies for securing funding and personnel support, modifying meal service approaches, enhancing hygiene and safety measures, organizing cross-district activities, promoting food waste utilization, and providing transportation services.